Update on vegetarian and vegan athletes: a review - Kenneth Vitale; Shawn Hueglin (Japanese Society of Physical Fitness and Sports Medicine, 2021)
Interest in vegetarian and vegan diets continues to grow, not only in the general population, but in the high-performing athlete. Vegetarian diets may lower risk of chronic diseases and have proposed ergogenic benefits to the athlete regarding exercise performance and enhanced recovery. However, controversy and confusion exist in the literature regarding vegetarianism. Traditionally, a vegetarian or vegan diet was considered low in certain micronutrients (iron, zinc, calcium, iodine, vitamin A, B2, B12, D), as well as protein, omega-3 fatty acids, and total energy needs. However, a vegetarian diet typically contains higher complex carbohydrates, dietary fiber, magnesium, nitrates, folic acid, vitamin C and E, carotenoids and other phytochemicals which may offer certain performance benefits to the athlete. This review summarizes the current literature on the benefits of a vegetarian diet specific to the athlete, clarifies nutritional requirements, and provides insight on the potential performance benefits. With proper meal planning, an athlete can meet all their nutritional needs with foods derived from plants without any loss in physical performance.